Hepatitis B virus infection and risk of coronary artery disease: A meta-analysis - Karn Wijarnpreecha (2018)
© Annals of Translational Medicine. All rights reserved. Background: Hepatitis B virus (HBV)-infected patients might be associated with coronary artery disease (CAD) from process of chronic inflammation. However, available studies yield conflicting results. This meta-analysis was performed to assess risk of CAD in HBV-infected patients. Methods: We searched MEDLINE and EMBASE for relevant literatures from database inception to June 2016. Studies comparing the risk of CAD among HBV-infected patients versus subjects without HBV infection using hazard ratio (HR), odd ratios, or relative risk (RR) were included. Random-effect model and generic inverse variance method were used to combine odds ratio (OR) and 95% confidence interval (CI). Results: A total of five studies, including three cross-sectional studies, one case-control study, and one cohort study, were subjected to analysis. The result demonstrates no significant risk of CAD among chronic HBV-infected patients and subjects without HBV infection (OR, 0.68; 95% CI, 0.40-1.13). Conclusions: This meta-analysis did not demonstrate a significantly increased risk of CAD among HBV-infected patients.